Acceptance-based process variables on postpartum well-being and distress: The mediating role of psychological flexibility. - Alexa Bonacquisti; Emily C Woodworth; Maria Diaz; Victoria A Grunberg (PLoS ONE)
Objective Although up to 20% of women experience postpartum depression and/or anxiety, current interventions are limited. Identifying the processes that impact outcomes can inform and enhance interventions. Our study aims to examine: (1) whether acceptance-based process variables (awareness, acceptance, cognitive defusion, psychological flexibility) were associated with postpartum outcomes; and (2) whether psychological flexibility mediated the relationship between treatment engagement and postpartum outcomes. Method Postpartum women (N = 266) were recruited online using snowball sampling via social media (i.e., Facebook). They completed a cross-sectional survey of validated and reliable quantitative measures assessing their well-being, emotional distress, and acceptance-based processes. Results Hierarchical regressions revealed that women with more awareness (β = .13; p = .023), acceptance (β = .17; p = .036), and cognitive defusion (β = -.46; p < .001) reported better well-being. When adding in psychological flexibility, cognitive defusion (β = -.24; p = .031) and psychological flexibility (β = -.33; p = .003) explained variance in well-being. Women with more acceptance (β = -.32; p < .001) and cognitive defusion (β = .52; p < .001) endorsed less emotional distress. When adding in psychological flexibility, acceptance (β = -.28; p < .001), cognitive defusion (β = .40; p < .001), and psychological flexibility (β = .18; p = .047) explained variance in emotional distress. Mediation models revealed that psychological flexibility explained the relationship between mental health treatment and well-being (b = 3.91, SE = 0.66, CI = [2.69, 5.30]) and emotional distress (b = -5.74, SE = 1.08, CI = [-1.26, 3.00]). Conclusions Targeting these acceptance-based processes in interventions may help to improve maternal, child, and family outcomes.